Can Community and School‐Based Supports Improve the Achievement of First‐Generation Immigrant Children Attending High‐Poverty Schools?. Issue 3 (29th March 2016) - Dearing, Eric; Walsh, Mary E.; Sibley, Erin; Lee‐St.John, Terry; Foley, Claire; Raczek, Anastacia E.
Abstract : Using a quasi‐experimental design, the effects of a student support intervention were estimated for the math and reading achievement of first‐generation immigrant children ( n  = 667, M  = 11.05 years of age) attending high‐poverty, urban elementary schools. The intervention was designed to help schools identify developmental strengths and barriers to learning and, in turn, connect children to community and school supports aligned with their strengths and needs. By exploiting within‐school changes in the implementation of the intervention, the present study revealed statistically and practically significant treatment effects indicating improvements in math and reading achievement at the end of elementary school. In addition, the intervention appears to considerably narrow achievement gaps between English language learners and immigrant children proficient in English.